Meat Yield and Length-Weight Relationship of Freshwater Crayfish (Pontastacus leptodactylus (Eschscholtz, 1823)) Population in Nine Different Inland Water Resources in Turkey - Selçuk Berber; Süleyman Akhan; Yusuf Bektaş; Gökhan Kalaycı (Acta Natura et Scientia)
In this research, length-weight relationships and meat yields of freshwater crayfish (Pontastacus leptodactylus) were investigated in Apolyont Lake, İznik Lake, Manyas Lake, Terkos Lake, Küçükçekmece Lake, Sera Lake, Çıldır Lake, Ulugöl Lake and Eğirdir Lake between July and September 2010. For this purpose, 698 individuals were sampled from nine different inland water resources in Turkey. a total of 62 individuals (34♀♀-28♂♂) from Apolyont Lake, 103 individuals (45♀♀-58♂♂) from İznik Lake, 129 individuals (85♀♀- 44♂♂) from Manyas Lake, 156 individuals (89♀♀-67♂♂) from Terkos Lake and 63 individuals (41♀♀-22♂♂) from Küçükçekmece Lake, 44 individuals (24♀♀-20♂♂) from Sera Lake, 34 individuals (13♀♀-21♂♂) from Çıldır Lake, 59 individuals (16♀♀-43♂♂) from Ulugöl Lake, and 48 individuals (25♀♀-23♂♂) from Eğirdir Lake were sampled during the field studies. For female individuals, the highest mean values for both carapace length and total weight were found in Manyas Lake as 52.34 mm, 34.16 g, respectively. For male individuals, the highest values for carapace length was found in Çıldır Lake as 61.34 mm, and the highest values for total weight was found in Apolyont Lake as 43.25 g. The results of the regression analyses indicated that allometric growth was found for both male and female individuals caught from Çıldır Lake, Sera Lake, Ulugöl Lake, and Eğirdir Lake. In addition, negative allometric growth was found for both male and female individuals caught from Manyas Lake, Terkos Lake and Küçükçekmece Lake, while positive allometric growth was found for male individuals caught from Apolyont Lake and İznik Lake and with regard to the carapace length-total weight relationship. For female specimens, the highest value for total meat yield was found in İznik Lake (19.76%) and the highest value for abdominal meat yield was found in Apolyont Lake (16.08%). Moreover, the highest values for both total meat yield and abdomen meat yield of male specimens were found in Sera Lake as 20.43% and 14.28%, respectively.